Revisiting Rachel Davis DuBois' Childhood and Young Adulthood: Reflections on the Linked Lives of an Intercultural Education Pioneer. Issue 1 (June 2018) - Mufti, Kathleen
Abstract : This paper presents a biographical analysis of the early life of Rachel Davis DuBois (1892–1993), an intercultural education pioneer of early twentieth-century America. The primary data source is DuBois' autobiography All This and Something More: pioneering in intercultural education . In a life course perspective, and guided by In Vivo Coding, this study focusses on the social relations linked to DuBois' childhood and early adulthood in order to better understand her participation in the intercultural education movement. I argue that evidence of her moral and political development are found in her Quaker ties and participation in the Quaker community during childhood and young adulthood. On the one hand, her adult emotional reaction to racial injustices may have stemmed from her experiences with hired workers on the farm; on the other hand, DuBois' Quaker upbringing and community influences may have impacted her pioneering role in the intercultural education movement.